Seroprevalence of Mycobacterium avium ssp. paratuberculosis in small ruminants in a flock in Antioquia, Colombia - Hernández-Agudelo, José Miguel; García-Tamayo, Yadi Marcela; Fernández-Silva, Jorge Arturo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Paratuberculosis is a chronic infectious disease caused by Mycobacterium avium ssp. paratuberculosis (MAP). This study aimed at determining the presence of antibodies against MAP, and the association between the serological status of MAP and individual factors in goats and sheep in a flock in Antioquia, Colombia. We studied fifty-three goats and 6 sheep over two years old, and took blood samples to obtain serum and information on individual factors. The presence of antibodies against MAP was determined by ELISA, whereas the information was descriptively analyzed. ELISA did not detect any positive or suspect animal among the 59 tested animals, so an association between serological status to MAP and individual factors could not be established. This is the first and the fourth study reporting the search for antibodies against MAP in a goat and in a sheep population in Colombia, respectively. Several factors may explain the serological status of the sampled animals. It is necessary to continue with similar studies in other flocks of the region and the country to determine the current MAP infection status in small ruminants in Colombia.